REDUCING WATER CONSUMPTION AND IMPROVING SOIL, ROOT QUALITY OF POTATO VIA ENVIRONMENTALLY SUSTAINABLE TREATMENTS - N. S. Dheyab; Aseel M.H. H. Al-Khafaji; I. J. Abdul Rasool; F. Y. Baktash; K. D. H. Al-jubouri; Z. J. Al-Mousawi; D. A. Hanoon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study aimed to improve potato plant productivity, roots growth biomass, and the efficiency of water utilization by using sustainable treatments .The experiment carried out at vegetable field of the College of Agricultural Engineering Sciences - University of Baghdad during spring season 2023. The experiment was conducted using split plot arrangement within Randomized Complete Block Design with two factors and three replicates (2X6X3). Applying TiO2-NPs represented the first factor (main plot) (10 mg.L-1), which symbolized (T0, T1). six treatments were included to represent subplots (regular irrigation interval (I) prolonged irrigation interval (D), fungal biofertilizers (DB), fungal biofertilizers + mannitol (DBM), fungal biofertilizers +xanthan (DBZ), fungal biofertilizers + mannitol+ xanthan (DBMZ). Results exhibited the superiority of spraying TiO2-NPs in all water use efficiency and yield traits. Also the results demonstrated the superiority of interaction treatment T1DBMX in producing significant results in nutrients concentrations and yield traits in compare to control treatment T0D.